Notes on the threadworm Strongyloides fuelleborni (Nematoda: Strongyloididae) in vervet monkeys (Chlorocebus pygerythrus) and zoonotic strongyloidiasis in southern Malawi - Alexandra Juhász; Peter Makaula; Lucas J. Cunningham; John Archer; Ruth Cowlishaw; Sam Jones; James E. LaCourse; Sekeleghe A. Kayuni; Janelisa Musaya; J. Russell Stothard (International Journal for Parasitology: Parasites and Wildlife)
We sought to ascertain whether zoonotic strongyloidiasis occurred in vervet monkeys (Chlorocebus pygerythrus), a non-human primate (NHP) species becoming increasingly common in Southern Malawi. Faecal collection took place in four locations: Nyala Park, a private wildlife reserve adjacent to a sugarcane plantation in Chikwawa District, and three public locations, each near tourist lodges in Mangochi District. Our sampling took place during July 2023, when 32 faecal samples were inspected with parasitological methods. After faecal culture, threadworm larvae were noted in both districts that were confirmed by molecular identification methods as Strongyloides fuelleborni, a first report for Malawi. Given the close spatial proximity of vervets with people, our findings affirm prior disease surveillance concerns of local zoonotic potential. We therefore encourage future targeted helminthological surveys for better local monitoring of strongyloidiasis in NHPs and people.